The Influence Of Brand Trust And Advertising On Purchasing Decisions And Repurchase Intentions - Kintan Kinari; Dwi Laras Karimah; Berliana Indah Pramesti; Agatha Citra V.D; Ricardo Indra (Jurnal Indonesia Sosial Teknologi, 2024)
The rapid development of the use of social media such as Instagram makes it easier for business people to market their products using the internet. It is not uncommon for marketing to be done via the internet and this marketing is better known through social media and has even become a trending product. Basically, marketing communication is carried out to gain the trust of the public through advertising or other programs. One of the marketing communication strategies carried out by companies using the internet is advertising. This advertising is carried out to obtain a certain goal such as purchasing decisions and repurchase intentions. Objective: To determine the influence of brand trust and advertising on purchasing decisions and repurchase intentions. Research design, data and methodology: Distributing online questionnaires via the Google online platform to 100 audiences who follow Dove's Instagram account. After all the data is collected, it is processed using Structural Equation Modeling Partial Least Squares. Results and Discussion: The research results found that brand trust and advertising have an influence on purchasing decisions and repurchase intentions.